Genetic and principal component analysis for agro-morphological traits, bioactive compounds, antioxidant activity variation in breeding lines of early Indian cauliflower and their suitability for breeding. Issue 1 (2nd January 2020) - Vanlalneihi, B.; Saha, P.; Kalia, P.; Singh, S.; Saha, N. D.; Kundu, A.; Singh, N.; Bhowmik, A.
ABSTRACT: This study was conducted to evaluate 16 early Indian cauliflower genotypes for agro-morphological traits, bioactive compounds and antioxidant activity. Analysis of variance, cluster analyses, and principal components analysis (PCA) elucidated patterns of variation among the genotypes. The genotype CC 12 exhibited highest marketable curd weight (450 g). Curd sinigrin varied from 3.29 to 16.37 µmol 100g −1 FW with maximum in DC 41–5. Total antioxidant capacity (CUPRAC and FRAP) ranged from 8.87 to 24.24 mg GAE 100g −1 and 11.71 to 34.00 mg GAE 100g −1 FW, respectively. The Phenotypic coefficient of variation (PCV) was higher than the Genotypic coefficient of variation (GCV) for all the characters with highest GCV, PCV and high heritability value for sinigrin content in curd. D 2 statistics classified the genotypes into three clusters where genotypes in cluster I had high sinigrin both in curd and leaf. The PCA revealed that first principal component (PC1) contributed 47.86% of total variation whereas, second principal component (PC2) contributed 35.14%. The genotypes Pusa Deepali, Selection 71, and CC 13 could be used in breeding programme for higher yield and bioactive compounds.